Cancel Culture among Indonesian Muslims on Social Media: Dynamics and Implications - Nurfitria, Nadia (Digital Muslim Review, 2024)
This article examines the phenomenon of cancel culture among Muslims in Indonesia, focusing on its manifestation on social media and its impact on divisions and perceptions of Islam. The study highlights prominent cases, including Ahok and Tuan Guru Mizan, which demonstrate how cancel culture fosters polarisation among conservative, moderate, and liberal Muslim groups, while reinforcing negative stereotypes of Islam as intolerant. Using qualitative methods and digital ethnography, I observe and documents the practice of cancel culture through the Trending Topic X and Google Trend features. It explores the dynamics of cancel culture, its implications for freedom of expression, and advocates for a dialogical approach rooted in Islamic values to address these challenges. This study aims to contribute to academic discourse on Digital Humanities within Islamic Studies and underscores the importance of fostering unity within Indonesia’s Muslim society.